The Effect of Autocratic Leadership, Emotional Support, and Ethical Leadership on the Performance of Generation Z Employees at PT Delta Majalengka - Putri Aisyah, Defani; Vikanie, Nawal; Mujahid Maolani, Fakhri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Employee performance is an important aspect in supporting the achievement of organizational goals, especially in companies dominated by Generation Z employees. This generation is characterized by its adaptability to change, yet it is also sensitive to leadership styles and the treatment they receive in the workplace. Differences in leadership styles and forms of support provided by leaders are believed to influence employee performance levels. This study aims to analyze the effects of autocratic leadership, emotional support, and ethical leadership on the performance of Generation Z employees at PT Delta Majalengka. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z employees at PT Delta Majalengka and analyzed using multiple linear regression analysis. The results indicate that autocratic leadership, emotional support, and ethical leadership have an effect on the performance of Generation Z employees. These findings suggest that the implementation of appropriate leadership styles, along with emotional support and ethical values in leadership, can enhance the performance of Generation Z employees.